Maqasid Al-Shariah Analysis of Marriage Annulment at the Cikarang Religious Court: A Case Study of Decision Number 1380/Pdt.G/2019/PA.Ckr - Suprihatin; Ema Damayanti; Musyaffa Amin Ash Shabah; Agus Supriyanto (Universitas Darunnajah Jakarta, Indonesia, 2025)
Marriage annulment due to fraudulent misrepresentation remains a critical yet under-examined phenomenon in Indonesian Islamic family law jurisprudence. This study aims to analyze the judge’s legal reasoning in Decision Number 1380/Pdt.G/2019/PA.Ckr at the Cikarang Religious Court concerning marriage annulment due to spousal fraud, and to evaluate the decision through the lens of maqasid al-shariah theory. This research employs a qualitative approach with normative-juridical legal research design. The primary data source consists of the court decision document, supplemented by statutory provisions and relevant Scopus-indexed scholarly literature. Data were analyzed through content analysis and the maqasid al-shariah framework at three hierarchical levels: daruriyyat, hajiyyat, and tahsiniyyat. The results demonstrate that the judge’s decision exhibits legal coherence with Article 27(2) of the Marriage Law and Article 72(2) of KHI regarding marriage annulment on grounds of fraud. Furthermore, the maqasid al-shariah analysis reveals that the annulment decision fulfills the five essential objectives (al-daruriyyat al-khams): protection of religion, life, intellect, lineage, and property. This study contributes to the growing body of literature on the intersection of Islamic legal philosophy and positive law application in Indonesian Religious Courts.